2022
DOI: 10.1039/d1cs00127b
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the grammar of Tau aggregation and pathology formation: how new insights from brain pathology are shaping how we study and target Tauopathies

Abstract: We discuss novel approaches for embracing and reproducing complexity of Tau pathology required for developing disease-relevant diagnostics and effective therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 600 publications
0
75
0
Order By: Relevance
“…Accordingly, we propose that Stg/Cdc25 comprise novel Tau phosphatases with strong impact on Tau biology and pathology, whose activity deserves further studies. Thus, Stg/Cdc25 adds to the list of key Tau regulators like Shaggy/GSK3-B (Jackson et al, 2002), Par-1/MARK (Ambegaokar and Jackson, 2011; Nishimura et al, 2004), MAPK and PP2A phosphatases (Shulman and Feany, 2003) identified in flies (reviewed in (Gistelinck et al, 2012; Hannan et al, 2016; Limorenko and Lashuel, 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, we propose that Stg/Cdc25 comprise novel Tau phosphatases with strong impact on Tau biology and pathology, whose activity deserves further studies. Thus, Stg/Cdc25 adds to the list of key Tau regulators like Shaggy/GSK3-B (Jackson et al, 2002), Par-1/MARK (Ambegaokar and Jackson, 2011; Nishimura et al, 2004), MAPK and PP2A phosphatases (Shulman and Feany, 2003) identified in flies (reviewed in (Gistelinck et al, 2012; Hannan et al, 2016; Limorenko and Lashuel, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in MAPT, the Tau encoding gene, and post-translational modifications (PTM), including phosphorylation, acetylation and ubiquitination, are the most common alterations associated with Tau pathology (Limorenko and Lashuel, 2022a; Tapia-Rojas et al, 2019). Recently, cryo-EM studies showed that cross-talk between PTMs underlies Tau structural diversity, impacts on fibril structure and correlates with distinctive tauopathies (Arakhamia et al, 2020; Fitzpatrick et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis, early detection, and early intervention are a significant and effective strategy [ 1 , 2 ]. The tau protein, as a defining characteristic of AD, is recognized as an important biomarker of AD [ 3 , 4 ]. The quantitative determination of the tau protein in cerebrospinal fluid (CSF) is the gold standard for the diagnosis of AD.…”
Section: Introductionmentioning
confidence: 99%